TUMMY TIME TERHADAP KEMAMPUAN MOTORIK BAYI : EVIDANCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Growth and development is a continuous process that occurs from conception and continues until adulthood. One of the early steps to accompany children's growth and development is to be carried out through stimulation. Stimulation to improve the motor ability to lift the baby's head is with tummy time exercise. Tummy time exercise is a term used for weight loss exercises by positioning the baby in a prone lying position to support the baby to actively perform cervical movements. Midwives have an important role in providing support and facilitating parents to do tummy time for their babies. Purpose: This evidence-based Case Report aims to determine the effect of tummy time on the baby's motor skills. Method: Evidance Based Case Report (EBCR), Search for articles regarding the effect of tummy time through Google Scholar and PubMed with the search keyword strategy Infant AND Tummy time AND Motoric. There were 3 articles that met the inclusion and exclusion criteria and had been previously screened, then critically reviewed. After being critically reviewed, it was stated that it was important and could be applied to. Result: This Evidence Based Case Report conducted on infants aged 15 days for tummy time 3 times a day for 3-5 minutes in 10 days by the parents. The baby's evaluation looked stronger when he raised his head. Conclusions: In this care, midwives are expected to be able to provide counseling and teach mothers about tummy time so that the implementation of care can be carried out by mothers.